Texas Almanac 2020-2021 - Willis, John (Editoral assistant); Muniz, Nathaniel; Hatch, Rosie; Plocheck, Robert (Book collections on Project MUSE., 2020)
The 70th edition in this long-running reference guide is filled to the brim with maps, statistics, full-color photographs, and fascinating information. You'll buy a piece of Texas history in every Texas Almanac in your collection. Our features this year include: Everyone knows Texas is a big state, but we continue to grow, sometimes in unexpected ways. Learn more about population growth, shifts, and trends, and where we might be by 2050 in this feature, written by Steve H. Murdock, Ph.D., a former director of the U.S. Census Bureau and currently a professor at Rice University and Director of the Hobby Center for the Study of Texas, and Michael Cline, Ph.D., former Associate Director of the Hobby Center for the Study of Texas. A new entry in our series on Texas immigrants focuses on Asian Indians. From facing early anti-Asian immigration bans to becoming the fourth largest concentration of Asian Indians in the United States, Indian Texans have helped shape the state's economy, public policy and cultural landscape. Learn about this rich immigration history and how the influence of Asian Indians can be felt across Texas. This feature is written by Ayshea Khan, Asian American Community Archivist at the Austin History Center. The entire book is revised with the latest information for every edition, including the 254 county maps and our population estimates for every Texas town. Chapters include: Environment: Learn about the geology of Texas, as well as in-depth information about plants, wildlife, rivers, and lakes. Weather: Highs and lows of the previous two years, plus a list of destructive weather dating from 1766. Also, a look at how our state has recovered since Hurricane Harvey. Astronomical Calendar: Find the moon phases, sunrise and sunset times, moonrise and moonset times, and any eclipses and meteor showers expected for 2020 and 2021. Recreation: The places to go visit in Texas, with details on state and national parks, landmarks, and wildlife refuges. Sports: The results of championship games for sports in Texas, from high school through professional, and a list of all Texas Olympic medalists and the past ten years of Texas Sports Hall of Fame inductees. Counties: An expansive section featuring detailed county maps, locator maps, and profiles of Texas' 254 counties. Population: Figures and the latest estimates from the State Data Center, plus an analysis of what has changed in the past 5-10 years and a comprehensive list of the population of Texas cities and towns. Elections: Results and maps from the 2018 General Election and information on voter turnout. Government: Historical documents and lists of governmental officials dating from our time under Spanish rule to today, as well as a recap of the 86th Legislative Session, information about state boards commissions, and lists of state, county, and local officials. Culture and the Arts: Find museums, competitions and award winners, and cultural and artistic highlights from the past few years, along with maps and data about the variety of religious groups in Texas. Business, Agriculture, and Transportation: Information about all aspects of our rich economy, and how we've faired as a state in the past few years, packed with tables about employment, prices, taxes, and more in a wide variety of industries. And much more....